Prognostic value of vascular remodeling parameters in the development of adverse cardiovascular events in patients with gastric cancer - Y. Yu. Kirichenko; I. S. Ilgisonis; P. A. Levin; Y. N. Belenkov (Российский кардиологический журнал, 2022)
Aim. To determine a possible prognostic marker for adverse cardiovascular events in patients with gastric cancer by studying the early and long-term effects of multiagent chemotherapy (MAC) on the structural and functional vascular wall parameters.Material and methods. The study included 25 patients with newly diagnosed gastric cancer who received courses of chemotherapy with platinum-based agents and fluoropyrimidines. All patients before, immediately after MAC courses and in the long-term period underwent a non-invasive assessment of vascular wall and endothelial function (photoplethysmography (PPG)). In the survivors’ cohort, a correlation analysis was performed to assess the risk of future cardiovascular events depending on changes of PPG parameters.Results. Before the MAC courses, cancer patients had endothelial dysfunction (mean occlusion index, 1,7 (1,4; 1,9), N>1,8) and structural vascular wall disorders (mean stiffness index, 8,9 m/s (7,7; 9,7), N<8 m/s, mean reflection index, 32,4% (27,5; 37,7), N<30%). All indicators significantly worsened after MAC in the form of endothelial dysfunction progression and vascular remodeling: mean occlusion index, 1,3 (1,2; 1,5) (p<0,0002), stiffness index, 10,3 m/s (9,5; 11,2) (p<0,0001), reflection index, 40,2% (35,5; 43,6) (p<0,001). Long-term follow-up averaged 2,9 years (2,3-3,7 years). All-cause and cardiovascular mortality was 32% and 12%, respectively. Nine patients developed a cardiovascular events (CVEs) (de novo, progression of prior CVD). Significant changes of vascular indicators in the long-term period was not revealed. A trend towards association between increased reflection index and a higher probability of cardiovascular pathology was revealed (OR 1,20, 95% CI 1,01-1,55, p=0,081).Conclusion. In this study, for the first time, a comprehensive assessment of the effect of MAC on endothelial dysfunction and vascular stiffness, including, in the long-term follow-up period, was carried out in patients with gastric cancer. A significant aggravation of all parameters of vascular remodeling immediately after treatment in the absence of their significant dynamics in the future has been proven. A possible prognostic marker, namely the reflection index, of an unfavorable cardiac outcome in patients with gastric cancer has been identified, which requires further study.